2017
DOI: 10.1002/jwmg.21212
|View full text |Cite
|
Sign up to set email alerts
|

Utility of radio‐telemetry data for improving statistical population reconstruction

Abstract: Statistical population reconstruction using age‐at‐harvest and catch‐effort data has recently emerged as a robust and versatile approach to estimating the demographic dynamics of harvested populations of wildlife. Although there are clear benefits to incorporating radio‐telemetry data into reconstruction efforts, these data are costly and time‐consuming to collect. Managers that consider collecting these data alongside existing efforts could benefit from a comprehensive examination of how such benefits are inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…An integrated population model using survey estimates combined with demographic data from the MNDNR studies may offer another approach to better understand trends in the population (Besbeas, Freeman, Morgan, & Catchpole, ). Reliance solely upon the survey to understand moose population dynamics will not be as informative or useful in the absence of demographic data gained from collaring studies, as has been demonstrated for fisher ( Pekania pennanti Erxleben 1777) and caribou ( Rangifer tarandus Linneaus 1758; Berg, Erb, Fieberg, & Forester, ; Murray et al, ; Serrouya et al, ). Collared animals are also needed to periodically recalibrate sightability models (Serrouya et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An integrated population model using survey estimates combined with demographic data from the MNDNR studies may offer another approach to better understand trends in the population (Besbeas, Freeman, Morgan, & Catchpole, ). Reliance solely upon the survey to understand moose population dynamics will not be as informative or useful in the absence of demographic data gained from collaring studies, as has been demonstrated for fisher ( Pekania pennanti Erxleben 1777) and caribou ( Rangifer tarandus Linneaus 1758; Berg, Erb, Fieberg, & Forester, ; Murray et al, ; Serrouya et al, ). Collared animals are also needed to periodically recalibrate sightability models (Serrouya et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The adult mortality rate has generally been decreasing, but later estimates could be biased due to weakened animals being culled from the population through predation or health-related mortality and stronger animals surviving to later years of the study. A relationship between collared adult survival rates and population-wide assessments of winter nutritional restriction suggests the condition of the collared animals was representative of that of the free-ranging population in the earliest years of the study Berg, Erb, Fieberg, & Forester, 2017;Murray et al, 2006;Serrouya et al, 2017). Collared animals are also needed to periodically recalibrate sightability models (Serrouya et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The AD model builder (Fournier ) has been used to fit many previous statistical population models (Broms et al , Fieberg et al ), but R, which has become widely used for statistical analysis, also has the capabilities to fit these models (Berg et al ). We found the maximum likelihood of the joint likelihoods using the nlminb function in the statistical software R (R Core Team ) and confidence intervals of the estimates using the profile likelihood method (Venzon and Moolgavkar ).…”
Section: Methodsmentioning
confidence: 99%
“…d and e are parameters to be estimated and describe the relation of survival to population density with a lag. these models (Berg et al 2017). We found the maximum likelihood of the joint likelihoods using the nlminb function in the statistical software R (R Core Team 2016) and confidence intervals of the estimates using the profile likelihood method (Venzon and Moolgavkar 1988).…”
Section: Without Change Point (Cp)mentioning
confidence: 99%
See 1 more Smart Citation